Two-phase treatment of patients with crossbite and tendency toward skeletal Class III malocclusion - Bayerl,Maria de Lourdes Machado (2014)
Angle Class III malocclusion is characterized by an inadequate anteroposterior dental relationship which may or may not be accompanied by skeletal changes. In general, patients are distressed by a significantly compromised facial aspect which, when associated with a deficient middle third, encourages patients to seek treatment. This article reports a two-phase treatment carried out in a female patient aged six years and six months with a tendency towards a Class III skeletal pattern. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO). It is representative of the Discrepancy Index (DI) category, and fulfills part of the requirements for obtaining BBO Diploma.